Implementation of Kahoot Digital Media in Increasing Student Engagement in IPAS Learning in Elementary Schools - Sari, Novita; Wahyudi, Syaiful Hasan; Sabilah Faradis, Umma Fatimah; Ning Dias, Gusti Imani; Hardiansyah, Framz (Journal of Practice Learning and Educational Development, 2026)
The purpose of this study is to determine the effectiveness of using the digital learning media Kahoot in assisting students at SDN Karang Anyar in learning Science and Social Studies (IPAS). This research is a qualitative descriptive case study involving fifth-grade students as subjects. Data were collected through observations, interviews with teachers and one staff member, ten students, as well as anecdotal notes during the learning process. The results of the study show that Kahoot has the ability to create an interactive and enjoyable learning environment, thereby significantly encouraging students to be more active and think critically in understanding IPAS material. Student responses vary according to each student's level of understanding; some students still experience difficulty following the material, while others have already understood it well. In addition, this study also found several technical obstacles such as limitations Technological devices and the lack of technological knowledge among students. However, teachers and parents respond that Kahoot has been proven useful as an interactive learning medium in elementary schools. For optimal implementation, adequate infrastructure support, teacher training, and parental supervision are required to ensure safe and successful digital learning.